**Answer:**

**Step-by-step explanation:**

4+9+14+...+494

d=9-4=5

\[a_{n}=a_{1}+(n-1)d\]

**Answer:**

The two numbers following 1,-2,3,-4,5... are -6 and 7.

**Step-by-step explanation:**

index: 1 2 3 4 5 ....

value: 1 -2 3 -4 5

Let the index be n. Then the first term is a(1), the secon is a(2), and so on.

a(2) = 2*(-1)^(2-1) = 2*(-1) = -2 (correct)

a(3) = 3*(-1)^(3-1) = 3*(-1)^2 = 3 (correct)

a(4) = 4*(-1)^(4-1) = 4*(-1)^3 = -4 (correct)

So the general formula for a(n) is: a(n)=n(-1)^(n-1)

Thus,

a(5) = 5(-1)^4 = 5

a(6) = 6(-1)^5 = -6

a(7) = 7(-1)^6 = 7

The "next two numbers in the pattern" are -6 and 7. The first 7 numbers are

1,-2,3,-4,5, -6, 7

**Answer:**

<h2>3.5</h2>

**Step-by-step explanation:**

Look at the picture.

If ABC is any triangle and AD bisects (cuts in half) the angle BAC, then

In our triangle we have the proportion:

We have

CB = 6

DB = 4.2

CA = 5

DA = x

Substitute:

<em>cross multiply</em>

<em>divide both sides by 6</em>